Controlled nano‐crystallization of IR frequency‐doubling Cd4GeS6 crystal in chalcogenide glass. Issue 8 (24th March 2020) - Ye, Qilin; Weng, Kaibo; Chen, Dan; Lin, Changgui
Abstract: Crystallization of IR frequency‐doubling nanocrystals in chalcogenide glasses is a promising approach to achieve novel nonlinear optical materials. However, controllable glass crystallization remains challenging. In this study, IR‐transparent chalcogenide glass‐ceramics containing novel Cd4 GeS6 IR frequency‐doubling nanocrystals (about 60‐80 nm) are fabricated through controlled nano‐crystallization. Nanocrystalline structure of the Cd4 GeS6 nano‐crystallized glass‐ceramics is investigated in detail through X‐ray diffractometer, field emission scanning electron microscope, and Raman scattering techniques. The structural similarity of [Cd4 GeS6 ] polyhedron in the network structure of as‐prepared glass is found to be responsible for the nucleation of Cd4 GeS6 crystal. A unique microstructure of Cd4 GeS6 nanocrystals embedded GeS2 phase‐separated structure is discovered in samples thermally treated at high temperatures (370°C and 380°C). This study would not only shed more light on glass crystallization mechanism but also provide a feasible approach for the design and fabrication of new IR frequency‐doubling materials through glass crystallization.